Elaboration and characterization of bioblends based on PVC/PLA. Issue 7 (24th October 2013) - Hachemi, Razika; Belhaneche‐Bensemra, Naima; Massardier, Valérie
Abstract With the aim to develop new biomaterials (bioblends) to be used in the field of waste elimination, this contribution focuses on the elaboration and characterization of new materials based on poly (vinyl chloride) (PVC) and poly (lactic acid) (PLA). The bioblends based on PVC/PLA were prepared by melt mixing in the absence and presence of maleic anhydride (MAH). The binary blends were first characterized in terms of thermal (glass transition temperature) and mechanical properties (tensile and micro‐hardness). Their thermal stability was investigated by thermogravimetric analysis (TGA). The results showed that this pair of polymers is not miscible and exhibited lower properties than those of the separated polymers. The in situ compatibilization was then performed using MAH and dicumyl peroxide (DCP) as an initiator. The presence of MAH enhanced the processability of the bioblends by decreasing the temperature of mixing. The properties of subsequent PVC/PLA bioblends were investigated through tensile and micro‐hardness testing, thermal analysis (DSC and TGA), and SEM. From the mechanical results, high level of compatibility was found when introducing MAH. The TGA studies indicated that the incorporation of PLA in PVC (matrix) increased thermal stability of the bioblend. Microscopic observations revealed uniformly dispersed PLA in the PVC matrix, confirming that phase separation has disappeared in the presence of MAH. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40045.